2022
DOI: 10.3389/fpsyt.2022.1003034
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations related to inflammation in suicidal ideation and behavior: A systematic review

Abstract: Background/objectivesImmune-inflammatory changes have been found in all types of suicidal ideation and behavior (SIB), independently of associated mental disorders. Since several Single Nucleotide Polymorphisms (SNPs) affect the function of inflammation-related genes, we searched the literature for genetic variations potentially altering inflammatory processes in SIB.MethodsWe included studies that looked for associations between SIB and SNPs in genes related to inflammatory processes. Case reports, literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Higher levels of IL-6 and other inflammatory cytokines have been reported in patients with MDD [ 59 ], and IL-6 levels decrease following cognitive behavioral therapy (CBT) intervention [ 60 ]. IL-6 is strongly associated with suicidal ideation and behavior [ 61 ]. Elevated IL-6 levels have been observed in the CSF of patients with MDD and in suicide attempters [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of IL-6 and other inflammatory cytokines have been reported in patients with MDD [ 59 ], and IL-6 levels decrease following cognitive behavioral therapy (CBT) intervention [ 60 ]. IL-6 is strongly associated with suicidal ideation and behavior [ 61 ]. Elevated IL-6 levels have been observed in the CSF of patients with MDD and in suicide attempters [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported, although inconclusive, findings regarding the potential association between suicidal phenotypes and variations in TGFB1 (encoding TGF-β1) [115] TNFA (encoding TNF-α) [116,117], TNF1B (encoding TNF-1β), IFNG (encoding IFN-γ) [117], IL1, IL1B (encoding IL-1β) and IL1RN (encoding Interleukin 1 Receptor Antagonist IL-1RA) [116,118], IL8 [119], and IL10 genes [68,117]. More recently, a systematic review of 32 studies investigating associations between suicidal behavior and SNPs in various inflammation-related genes reported that most frequently investigated genes included TNFα, IFNγ, ACP1, IL1β, IL8, IL10, IL1A, IL7, TGFB1 and MIF (encoding macrophage migration inhibitory factor) and found that polymorphisms in IL8 (rs4073), CRP (rs1130864), TNFa (rs1800629, rs361525, rs1099724), TNFRII (rs1061622), TGFB1 (rs1982073), ACP1 (encoding Acid Phosphatase 1) (rs7419262, rs300774), IL10 (rs1800896), IFNG (rs2430561), ACMSD (encoding aminocarboxymuconate semialdehyde decarboxylase) (rs2121337), IL7 (rs10448044, rs10448042), MIF (rs755622), IL1A (rs1800587), and IL1B (rs1143634, rs16944) are likely to be associated with suicidality [120]. However, it must be borne in mind that the reliability and scientific value of candidate gene studies have recently been questioned in part due to their low replicability leading to the abandonment of this approach [121].…”
Section: Inflammatory and Cytokine Genetic Markers Of Suicidal Behaviormentioning
confidence: 99%
“…However, it must be borne in mind that the reliability and scientific value of candidate gene studies have recently been questioned in part due to their low replicability leading to the abandonment of this approach [121]. GWAS studies also stressed some relevant findings, such as rs300774 in ACP1 with a genome-wide significance, and several suggestively significant variants such as rs10903034 (IL28RA), rs1467558 (CD44), rs6480463 (ADAMTS14), rs4575 (PSME2), rs10448042 and rs10448044 (IL7) [120]. Furthermore, based on data from large GWAS-s, a Mendelian randomization study reported that the upregulation in IL-6 signaling is a potential causal risk factor of suicidality, also suggesting that overactivity of IL-6 may be associated with suicidal behavior, suggesting that IL-6 blockade may be a potential novel treatment or preventive target [64].…”
Section: Inflammatory and Cytokine Genetic Markers Of Suicidal Behaviormentioning
confidence: 99%